Zespół Metaboliczny cz. II: Epidemiologia zespołu metabolicznego w Polsce i na świecie = Metabolic Syndrome part II: Epidemiology of metabolic syndrome in Poland and in the World - Kalinowski, Paweł; Mianowana, Maryla (Journal of Education, Health and Sport, 2016)
Kalinowski Paweł, Mianowana Maryla. Zespół Metaboliczny cz. II: Epidemiologia zespołu metabolicznego w Polsce i na świecie = Metabolic Syndrome part II: Epidemiology of metabolic syndrome in Poland and in the World. Journal of Education, Health and Sport. 2016;6(4):466-480. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50681 http://ojs.ukw.edu.pl/index.php/johs/article/view/3497 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 28.04.2016. Zespół Metaboliczny cz. II: Epidemiologia zespołu metabolicznego w Polsce i na świecie Metabolic Syndrome part II: Epidemiology of metabolic syndrome in Poland and in the World Paweł Kalinowski1, Maryla Mianowana2 1. Samodzielna Pracownia Epidemiologii Uniwersytet Medyczny w Lublinie, Staszica 4/6, 20-081 Lublin 2. Oddział Kardiologii – Pododdział Intensywnego Nadzoru Kardiologicznego, Wojewódzki Szpital Specjalistyczny im. Stefana Kardynała Wyszyńskiego, Al. Kraśnicka 100, 20-718 Lublin Słowa kluczowe: zespół metaboliczny, insulinooporność, choroby sercowo-naczyniowe, choroba niedokrwienna serca Key words: metabolic syndrome, insulin resistance, cardio-vascular diseases, coronary heart disease Streszczenie Zespół metaboliczny jako czynnik ryzyka rozwoju chorób sercowo-naczyniowych i cukrzycy typu 2, jak pokazują liczne badania, jest znacznie rozpowszechniony zarówno w Polsce jak i w Europie oraz na innych kontynentach. Od lat prowadzone są badania, która definicja zespołu metabolicznego ma najlepszą wartość prognostyczną i diagnostyczną. W zależności od kryteriów stosowanych w różnych definicjach, a także od charakterystyki badanej populacji, częstość występowania zespołu metabolicznego jest różna. Niezależnie od kryteriów jest ona wysoka i wciąż rośnie. Celem pracy było przedstawienie rozpowszechnienia zespołu metabolicznego w Polsce i innych krajach, jako czynnika ryzyka chorób układu sercowo-naczyniowego na podstawie danych dostępnych z piśmiennictwa. Według badań przeprowadzonych w Polsce zespół metaboliczny dotyczy około 20% dorosłej populacji, czyli około 5,8 miliona mieszkańców Polski, częściej występuje u kobiet niż u mężczyzn. Na świecie problem ten może dotyczyć nawet 33% populacji Stanów Zjednoczonych, 27% populacji Chin, w Europie zawiera się pomiędzy ok. 15% (Francja) do około 34 % populacji (Włochy, Finlandia). Zespół metaboliczny wiąże się ze zwiększoną częstością występowania cukrzycy, zdarzeń sercowo-naczyniowych i śmiertelności, według wielu badań 2,5-krotnie zwiększa ryzyko wystąpienia zawału mięśnia serca, powoduje 1,5-krotny wzrost śmiertelności całkowitej i 2-krotny wzrost incydentów sercowo-naczyniowych. Summary As numerous studies have shown, metabolic syndrome as a risk factor for cardiovascular disease and type II diabetes is widely spread, both in Poland and Europe and on other continents. The research work aiming at determining which definition of the metabolic syndrome has the best predictive and diagnostic value has been conducted for many years. The prevalence of metabolic syndrome differs depending on the criteria used in various definitions, as well as the characteristics of the examined population. Yet, irrespective of the criteria, its level remains high and is still growing. The aim of the current study is to present the prevalence of metabolic syndrome (as a risk factor for cardiovascular disease) in Poland and other countries on the basis of information available from the reference literature. According to the studies conducted in Poland metabolic syndrome affects approximately 20 % of the adult population, that is approximately 5.8 mln. residents of Poland. It occurs more often in women than in men. Worldwide this problem might involve as much as 33% of the USA population, 27% of China’s population, and in Europe this varies between approximately 15% (France) and approximately 34% of the population (Italy, Finland). Metabolic syndrome is connected with an increased incidence rate of diabetes, cardiovascular events and mortality rate; according to many studies it raises the risk of myocardial infarction 2.5-fold, and causes a 1.5-fold increase in the total mortality rate and a 2-fold increase of the number of cardiovascular events.